(untitled) (Studia Prawnicze / The Legal Studies, 1999)
Wykładnia porównawcza § 1 zd. 2 - regulującego skład komisji i § 2 art. 23712 § 2 k.p. - określającego, kto przewodniczy komisji, przy zwróceniu uwagi na takie sformułowania ustawowe dotyczące czynności faktycznych czy prawnych jak: współdziałanie komisji z pracodawcą jako jedno z jej zadań (art. 23713 § 1 k.p. in fine), czy możliwość uzgodnienia przez komisję z pracodawcą, że zasięgnie ona opinii specjalistów spoza zakładu pracy (art. 23713 § 3 k.p.) prowadzi do konkluzji, że ustawodawca traktuje pracodawcę (przedstawiciela pracodawcy) jako podmiot zewnętrzny wobec komisji, tj. taki, który chociaż jej przewodniczy, nie wchodzi w jej skład na statusie członka. Z ustaniem stosunku pracy, nie tylko w wyniku śmierci pracownika, mandat członka komisji bhp wygasa. Polecenia wydane członkom komisji bhp, którzy są pracownikami, w realizacji funkcji przewodniczenia mieszczą się w granicach kierownictwa, określonych w art. 100 § 1 k.p. Tak więc konieczna treść upoważnienia, którego pracodawca może udzielić innej osobie (art. 23712 § 2 k.p.) powinna obejmować, co wynika z przyjętych założeń, prawo wydawania poleceń (wskazówek) mających na celu realizację funkcji przewodniczenia. Wiceprzewodniczenie komisji bhp przez społecznego inspektora pracy nie mieści w sobie możliwości zastępowania pracodawcy (osoby upoważnionej) w realizacji uprawnienia do wiążącego kierowania (z zewnątrz) pracami komisji, a polega jedynie na zastępstwie w postaci udzielania przewodniczącemu pomocy w wykonywaniu jego zadań. Pracodawca - będąc przewodniczącym - kieruje pracami komisji. Zarazem jednak nie wchodzi w jej skład i pozostaje podmiotem wobec niej zewnętrznym. Pracodawcy nie przysługują zatem kompetencje, jakie posiada każdy członek komisji z osobna i komisja jako całość. O ile przeto członek komisji ma obowiązek realizować polecenie (wskazówkę) pracodawcy, które dotyczy spraw czysto formalnych, o tyle członek komisji czy wszyscy członkowie mogą odmówić wykonania polecenia (wskazówki), które ingerowałoby w kwestie merytoryczne. Te bowiem zastrzeżone zostały tylko dla komisji, a nie także dla jej zewnętrznego przewodniczącego. Przewodniczący ten ma obowiązek uwzględniać autonomię komisji w sprawach merytorycznych, którą ustawodawca jej przyznał. Dlatego pracodawcy nie tylko nie przysługuje kompetencja do brania udziału w głosowaniu nad np. projektem wniosku (zob. art. 23713 § 1 k.p. in medio), ale i nie może on wiążąco określać problemów związanych z bhp w zakładzie, które miałyby być przedmiotem obrad. Jego zadaniem będzie wyłącznie ułożenie, w miarę możliwości, takiego porządku obrad nad kwestiami ustalonymi przez komisję, który zapewni sprawny przebieg posiedzenia. Nie wyklucza to prawa przewodniczącego do zaproponowania komisji określonego problemu związanego z bhp jako ewentualnego przedmiotu obrad. Arbitralne przyjmowanie trybu wyboru przedstawicieli pracowników przez pracodawcę stanowi naruszenie przepisu art. 23712 § 1 zd. 2 k.p. Obligatoryjna treść aktu przyjmującego tryb wyboru nie została zakreślona przez ustawodawcę. Wydaje się jednak, że podmioty dokonujące ustaleń powinny - na wzór art. 245 k.p. regulującego przedmiot uzgodnień podjętych przed powołaniem komisji pojednawczej - określać co najmniej: liczbę przedstawicieli pracowników, sprecyzować, komu przysługuje czynne i bierne prawo wyborcze, wyznaczyć końcowy termin, do którego należy dokonać wyboru. Ścisła wykładnia przepisu art. 23712 § 1 zd. 2 k.p. odnośnie do kompetencji zakładowej o.z. prowadzi również do wniosku, że pracownikom przysługuje bezpośrednia kompetencja do odwołania przedstawiciela (o ile taką możliwość, w sytuacji mandatu udzielonego na określony czas, dopuszcza w danym przypadku porozumienie między zakładową o.z. a pracodawcą). A comparative interpretation of § 1 clause 2 that governs the composition of the committee and § 2 of Article 23712 § 2 of the Labour Code specifying who chairs the committee, pointing out the such statutory wording for de facto or de jure actions as: the committee’s interaction with the employer as one of its tasks (Article 23713 § 1 Labour Code in fine), or the possibility for the commission to agree with the employer that it will consult experts from outside the workplace (Article 23713 § 3 of the Labour Code) leads to the conclusion that the legislator treats the employer (the employer’s representative) as an entity external to the commission, i.e. one that, although it chairs the commission, is not part of it in the status of a member. With the termination of the employment relationship, not only as a result of the death of the employee, the mandate of the member of the health and safety committee expires. The instructions given to the members of the health and safety committee, who are employees, in the performance of their chairmanship function fall within the limits of management, as defined in Article 100 § 1 of the Labour Code. Thus, the necessary content of the authorisation that the employer may grant to another person (Article 23712 § 2 of the Labour Code) should include, as is assumed, the right to give instructions (directions) aimed at the performance of the presiding function. The vice-chairmanship of the health and safety committee by the social labour inspector does not include the possibility to substitute the employer (authorised person) in the exercise of the power to give binding direction (from outside) to the work of the committee, but consists only of substitution in the form of assisting the chairman in the performance of their tasks. The employer, being the chairman, directs the work of the committee. At the same time, however, it is not part of it and remains an entity external to it. The employer is therefore not entitled to the powers that each member of the committee individually and the committee as a whole has. While, therefore, a committee member is obliged to follow an order (direction) of the employer which concerns purely formal matters, a committee member or all members may refuse to follow an order (direction) which would interfere with matters of substance. This is because these have been reserved only for the committee and not also for its external chairman. Such chairman is obliged to take into account the autonomy of the committee in matters of substance which the legislature has granted it. Therefore, the employer is not only not entitled to take part in the vote on, for example, a draft proposal (see Article 23713 § 1 Labour Code in medio), but neither can it be binding on the OSH problems in the establishment that were to be discussed. His or her task will be solely to arrange, as far as possible, an agenda on the issues set by the committee that will ensure the smooth running of the meeting. This does not exclude the chairman’s right to propose a specific OSH problem to the committee as a possible subject for discussion. The arbitrary adoption of the mode of selection of employee representatives by the employer constitutes a violation of the provision of Article 23712 § 1, clause 2 of the Labour Code. The obligatory content of the act adopting the selection procedure has not been specified by the legislator. However, it would seem that those making the arrangements should – along the lines of Article 245 of the Labour Code, which regulates the subject matter of the arrangements made prior to the establishment of the conciliation committee – specify at least: the number of employee representatives; specify who has active and passive electoral rights; set a final deadline by which the election must be made. A strict interpretation of the provision of Article 23712 § 1 clause 2 of the Labour Code with regard to the competence of the company’s trade union also leads to the conclusion that the employees have a direct competence to dismiss the representative (insofar as such a possibility, in the situation of a mandate granted for a certain period of time, is allowed in the case in question by an agreement between the trade union and the employer).